Production economics of wild honey collection industry in Kedah, Malaysia - Johnny, Mariani (2015)
Wild honey is an important Non – Timber Forest Product for communities residing near the tropical forests in Malaysia, contributing lucrative additional household incomes. Yet spotting trees with honey bee hives is getting scarcer and climbing these trees extremely dangerous to the novice. This led the interest of investigating the socioeconomic and the production economics of this small scale honey gathering industry, covering Pedu and Ulu Muda forests and villages surrounding them in Kedah. The objectives of this study are i) to obtain the socioeconomic profile of the collection team and marketing chain of wild honey in Kedah and ii) to estimate the production functions of wild honey collection. For the first objective, statistical tests have been used to differentiate the socioeconomic profile and marketing chains of the wild honey collections from trees in the natural forest versus trees in surrounding villages. While for the second objective, two models have been specified which are the Cobb Douglas and Translog production functions. The study found that there were statistical differences in collection processes, yield and sales between the two sources. The production functions showed that the number of labor days and number of trees were statistically significant factors in influencing honey yield. The industry shows increasing returns to scale for the Cobb Douglas production function while it was decreasing returns to scale for the Translog function. Comparing the value marginal products of inputs with their marginal factor costs suggests that raising the inputs could raise greater returns to the collection team. Hence given the potential lucrative returns, raising forest conservation could ensure the sustainability of the wild honey collection industry. As for marketing, the role of government agencies such as the Federal Agricultural Marketing Authority could ensure collectors of a ready market for the industry.